Partridge tea polyphenols alleviated STZ-induced diabetic nephropathy by regulating Keap1/Nrf2/ARE signaling pathway in C57BL/6 mice - Mantong Zhao; Keke Meng; Meihui Zhao; Haohao Shi; Zhongyuan Liu; Yonghuan Yun; Weimin Zhang; Zhouwei Duan; Guanghua Xia (Journal of Functional Foods, 2024)
The present work investigated the effect of Partridge tea polyphenols (PTP) on streptozotocin (STZ)‑induced diabetic mice as well as the underlying mechanism with rosiglitazone as positive control. Administration with PTP (250 or 500 mg/kg) for 5 weeks, compared to the diabetic nephropathy control group (DC group), PTP significantly decreased the renal index, creatinine in serum and urine, urea nitrogen and proteinuria and alleviated histopathological injury of renal tissue. The levels of TNF-α, IL-1β and IL-6 were decreased and SOD, CAT activities were increased by PTP. PTP significantly reduced the FN and COL-IV levels. Moreover, PTP significantly inhibited the Keap1 mRNA level of Keap1 and the corresponding protein expression, while increased the mRNA levels of Nrf2, HO-1, NQO1 and the corresponding protein expression. Therefore, PTP could reverse renal injury, enhance renal functions, inhibit renal oxidative stress, and activate Keap1/Nrf2/ARE signaling pathway to alleviative diabetic nephropathy.